May Measurement Month 2019: an analysis of blood pressure screening results from Spain. (20th May 2021) - Molinero, Ana; Calvo, Eva; Beaney, Thomas; Day, Emily; Prats-Mas, Rosa; Fornos, José A; Mera-Gallego, Inés; Tous, Salvador; de Andrés, Nicanor F; Rodilla, Enrique; Gijón, Teresa; Pérez-Manchon, David; et al.
Abstract: The aim of the May Measurement Month (MMM) is devoted to better understanding the awareness, treatment, and control rates of hypertension in Spain. Presented here are the data corresponding to 2019 campaign. In 2019, a total of 4433 patients (61.5% males) with a mean age of 54.8 years were included. Of all, 96.0% were Caucasian, and 3294 were recruited in pharmacies. The mean values of systolic blood pressure (BP) were 125.6 and of diastolic 76.7 mmHg in the whole population. The most recent previous BP measurement took place more than 1 year before in 27.6% of participants. A total of 1883 were hypertensive (systolic BP ≥140 mmHg or diastolic BP ≥90 mmHg or taking antihypertensive medication), of whom 77.2%/were aware and 71.1% were on medication. Of all, 64.9% of those on medication and 46.1% of all hypertensive participants had a BP controlled to <140/90 mmHg. These data from MMM 2019 continue to indicate the need for an improvement in the awareness, treatment, and control of hypertension in Spain.